ABT-263, a BCL-2 inhibitor, selectively eliminates latently HIV-1-infected cells without viral reactivation. - Jeong Eun Kang; Hyun Wook Seo; Dong-Eun Kim; Young Hyun Shin; Songmee Bae; Cheol-Hee Yoon (PLoS ONE)
Human immunodeficiency virus-1 (HIV-1) is a hazardous pathogen responsible for causing acquired immunodeficiency syndrome (AIDS). HIV-1 provirus survives in latently infected cells for a long time, despite treatment with combinational anti-retroviral therapy (cART); therefore, it is considered as a major obstacle in HIV-1 treatment. Several strategies have been developed to selectively eliminate latently HIV-1-infected cells; however, clinical success has not yet been reported. Here, we identified several key factors associated with cell apoptosis, which were upregulated in latently infected cells. Subsequently, we screened compounds targeting these factors to selectively kill latently HIV-1-infected cells. Among these, ABT-263 (Navitoclax), a BCL-2 inhibitor, exhibited a potent and selective killing effect on latently HIV-1-infected cells and exerted synergistic effects with combinations of other compounds targeting myeloid cell leukemia-1 (MCL-1), X-linked inhibitor of apoptosis protein (XIAP), and BAX. In an ex vivo model, latently HIV-1-infected memory CD4+ T cells were efficiently eliminated via treatment with ABT-263 alone and its combinations with other modulatory compounds. Taken together, our results demonstrate that the balance of pro- and anti-apoptotic factors is crucial for the survival of latently HIV-1-infected cells. Thus, disrupting this balance using ABT-263 or combinations having ABT-263 without proviral reactivation may be useful for developing a novel strategy to eliminate latently infected cells in individuals infected with HIV-1.